\(a^2=by+cz\)
বা, \(a^2+ax=ax+by+cz\)
বা, \(a(a+x)=ax+by+cz\)
বা, \(a+x=\cfrac{ax+by+cz}{a}\)
আবার, \(b^2=cz+ax\)
বা, \(b^2+by=ax+by+cz\)
বা, \(b(b+y)=ax+by+cz\)
বা, \(b+y=\cfrac{ax+by+cz}{b}\)
এবং, \(c^2=ax+by\)
বা, \(c^2+cz=ax+by+cz\)
বা, \(c(c+z)=ax+by+cz\)
বা, \(c+z=\cfrac{ax+by+cz}{c}\)
\(\therefore \cfrac{x}{a+x}+\cfrac{y}{b+y}+\cfrac{z}{c+z}\)
\(=\cfrac{x}{\cfrac{ax+by+cz}{a}}+\cfrac{y}{\cfrac{ax+by+cz}{b}}\)
\(+\cfrac{z}{\cfrac{ax+by+cz}{c}}\)
\(=\cfrac{ax}{ax+by+cz}+\cfrac{by}{ax+by+cz}\)
\(+\cfrac{cz}{ax+by+cz}\)
\(=\cfrac{ax+by+cz}{ax+by+cz}\)
\(=1\) (প্রমাণিত)